Quantum Databases: Leveraging Quantum Computing for Advanced Queries - Sayantan Saha, (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
This article explores the transformative potential of quantum computing in database systems, focusing on advanced query operations that traditionally challenge conventional architectures. It examines how quantum mechanical phenomena like superposition and entanglement enable unprecedented parallel processing capabilities in database operations. The article investigates key areas including pattern matching, similarity searches, and graph traversal algorithms, where quantum advantages show particular promise. It compares quantum and classical systems, addressing scalability considerations and accuracy challenges in quantum database implementations. The article delves into hybrid quantum-classical architectures and quantum native approaches, examining their respective strengths and limitations. Special attention is given to the challenges and opportunities presented by Noisy Intermediate-Scale Quantum (NISQ) devices, including hardware limitations, algorithm development, and practical integration considerations. The article provides insights into the future directions of quantum databases, emphasizing the importance of developing robust error correction mechanisms and optimizing quantum circuits for practical database operations.
Keywords: Quantum Database Systems; Quantum Error Correction; Hybrid Quantum-Classical Architecture; Quantum Search Algorithms; NISQ Computing